The strategy versus the direct-response method: a first survey of experimental comparisons - Brandts, Jordi; Charness, Gary (Experimental economics : a journal of the Economic Science Association, 2011)
In this paper, we present a first survey of the literature regarding whether the strategy method, in which a responder makes conditional decisions for each possible information set, leads to different experimental results than does the more standard direct-response method, in which the responder learns the action of the first mover and then chooses a response. Of the twenty-nine existing comparisons, sixteen find no difference, while four do find differences, and nine comparisons find mixed evidence. We also find some indications about the underlying determinants of when the two methods lead to different responses. For example, it appears that levels of punishment are substantially lower with the strategy method. In addition, it also appears that difference across these elicitation methods are more likely when people make fewer contingent choices. Finally, in no case do we find that a treatment effect found with the strategy method is not observed with the direct-response method.